Research on China’s adolescent mental health policies — analysis based on PMC index model - Yang, Chengning (Frontiers in Public Health, 2024)
In recent years, the suicide rate among adolescents in China has shown a continuous upward trend, and mental health issues such as depression and excessive anxietycampus bullying and adolescent violence have become increasingly prominent. In 2023, the Chinese Ministry of Education, in collaboration with 17 other national government departments including the National Health Commission, issued the National Special Action Plan for Student Mental Health Work, marking the rise of China's efforts to strengthen adolescent mental health education as a national strategy.Awareness and concerns around poor mental health in adolescents is rising amongst the general public and in academic circlesThe attention of social public opinion and academic circles continues to rise, but there is little research on adolescent mental health policies in China. This article reviews the national policies on adolescent mental health from 2000 to 2023, and analyzes and evaluates the selected policy texts through the PMC index model. The results showed that while feasibility and synergy of policy are improving overall, there is a lack of promotional and supervisory policies in the policy-making process; a lack of legislative protection; and a lack of detailed planning. Based on these findings, targeted policy recommendations have been proposed in combination with the China's situation.The results showed that the feasibility and synergy of policies are improving overall, but there is also a lack of promotional and supervisory policies in the policy-making process; Lack of legislative protection; Lack of detailed planning and basis, and based on this, targeted policy recommendations have been proposed in combination with the domestic situation.